2010
DOI: 10.1007/s10144-010-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

Belowground microbial symbiont enhances plant susceptibility to a spider mite through change in soybean leaf quality

Abstract: To examine how rhizobia affect the chemical and nutrient status in leaves of soybean (Glycine max L.), and how rhizobia change plant susceptibility to a generalist spider mite (Tetranycus urticae), we cultivated root-nodulating soybeans (R?) and their non-nodulating mutant (R-) in a common garden. We experimentally fertilized the plants with nitrogen to examine effects of rhizobia on the plant traits and plant susceptibility to spider mites at different nitrogen levels. R? plants produced more leaves containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 67 publications
0
25
0
2
Order By: Relevance
“…90 is closely related to Fujimishiro except for root nodulation. In another potted plant experiment, Katayama et al (2010) showed that the number of root nodules of the R+ plants was 82.4 ± 8.6 (mean ± SE, n = 15), but there were no nodules on the roots of the R− plants ( n = 24). Also, foliar nitrogen and phenolics of the R+ plants were 50% higher and 12% lower than those of the R− plants in the presence of rhizobia.…”
Section: Methodsmentioning
confidence: 95%
“…90 is closely related to Fujimishiro except for root nodulation. In another potted plant experiment, Katayama et al (2010) showed that the number of root nodules of the R+ plants was 82.4 ± 8.6 (mean ± SE, n = 15), but there were no nodules on the roots of the R− plants ( n = 24). Also, foliar nitrogen and phenolics of the R+ plants were 50% higher and 12% lower than those of the R− plants in the presence of rhizobia.…”
Section: Methodsmentioning
confidence: 95%
“…The enhanced species richness and abundance of insect herbivores are most likely due to increased foliar nitrogen in plants with rhizobia (Katayama et al, 2010).…”
Section: Induced Nutritional Qualitymentioning
confidence: 99%
“…Such beneficial processes of Rhizobium are affected by biotic factors like rhizosphere microbes (van Veen et al, 1997) as well as abiotic factors like soil fertility (Rotaru & Sinclair, 2009). Belowground colonization of roots by Rhizobium has been found to interact with aphids and other aboveground herbivores (Kempel et al, 2009;Katayama et al, 2010Katayama et al, , 2011Martinuz et al, 2012). For example, root colonization by Rhizobium has been found to promote plant resistance to insect pests (Thamer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%